Intensity and Type of Physical Activity and Semen Quality in Young Healthy Men Living in Brescia, North Italy (Epidemiology, Biostatistics, and Public Health, 2025)
INTRODUCTIONA decline in semen quality has been documented over recent decades, possibly linked to rising rates of obesity, unhealthy diets, and exposure to environmental toxins, although the exact causes remains a topic of debate [1]. Recreational physical activity (PA) has been associated with numerous heath benefits, including the prevention of chronic diseases and the promotion of overall well-being, and it is strongly recommended by the World Health Organization (WHO) and various Scientific Societies.Physical activity is hypothesized to have a positive effect on semen quality due to its favorable impact on metabolic and endocrine functions [2]. However, excessive physical activity may have the opposite effect, potentially leading to reduced semen quality and fertility. This may be due to impaired function of the hypothalamic-pituitary-gonadal axis, increased oxidative stress, and chronic inflammation [3–5].AIMSTo investigate this topic and add evidence, we conducted a cohort study aimed to assess the relationship between PA intensity and semen quality – measured by sperm concentration, total and progressive motility, and proportion of normal morphology cells - in a population of healthy young men living in Brescia, North Italy.MATERIALS AND METHODSA prospective study within the FAST randomized trial was conducted between April 2018 and June 2019 [6]. Semen quality parameters were assessed at the enrollment (baseline) and again after 4 and 8 months. Each semen sample was collected in a sterile container via masturbation after a period of sexual abstinence lasting at least 3 days and no more than 5 days. Samples were delivered to the laboratory within 30–40 minutes of collection, and a portion of each sample (